Strengthening Human Resource Readiness Regarding Automated Container Terminals (ACT) For Port Service Optimization (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
An introduction to ACT technology is the first step in preparing competent human resources ready to face the era of digital ports. This activity aims to equip students, faculty members, port practitioners, and relevant stakeholders with insights into the components of ACT and integrated terminal management systems. This community service activity was conducted using a participatory method that combined lectures, interactive discussions, technology demonstrations, and case studies. The activity was carried out through several structured and systematic stages, including: the Preparation Stage, the Participant Recruitment Stage, the Activity Implementation Stage, the Evaluation and Reporting Stage, and the Follow-up and Program Sustainability Stage. The event was attended by 127 participants, comprising students from the Mechanical Engineering, Nautical Science, and Port and Waterway Engineering programs, faculty members, as well as port practitioners and representatives from related agencies. The outreach activity enhanced participants’ understanding of various aspects of Automated Container Terminals. Participants were highly interested in Automated Guided Vehicle (AGV) technology, which can operate non-stop without an operator; Automated Stacking Cranes (ASC), capable of stacking containers with high precision; and Remote-Controlled Quay Cranes, which can be operated from a control room located far from the pier. This event not only provided theoretical knowledge but also broadened participants’ perspectives on career opportunities and the competencies required to navigate the era of digital transformation in the port sector.